Concrete for brake bed of highway emergency lane as well as preparation method and application of concrete
By using a specific proportion of concrete in the brake bed of the highway emergency lane, the problems of limited deceleration effect, high maintenance cost and poor adaptability of existing materials are solved, and high-efficiency, low-cost and good adaptability braking is achieved. Effect.
Patent Information
- Application Number
- CN202411292716.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing highway hedge lane brake bed materials have problems such as limited speed reduction effects, high maintenance costs and poor adaptability, which are difficult to meet the actual needs of highway safety management.
A kind of concrete for highway emergency lane brake bed is used. Its components include cement, carbon mineralized mineral materials, lightweight aggregate, modified fiber, foaming agent, foam stabilizer and water reducing agent. Through specific Proportions and preparation methods to optimize the pore structure and performance of concrete.
The prepared concrete has long-term stable collapse energy absorption, excellent maximum crushing depth and friction coefficient, which can effectively buffer the impact of accident vehicles, reduce use costs, and improve construction efficiency and overall structural stability.
Smart Images

Figure BDA0005045082290000051 
Figure BDA0005045082290000071 
Figure BDA0005045082290000081
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete, and in particular to concrete for a brake bed of a highway escape lane, and a preparation method and application thereof. Background Art
[0002] As an important part of modern transportation, the safety and efficiency of highways are of great significance to the development of social economy. However, due to the high speed of vehicles on highways, serious traffic accidents are very likely to occur when vehicles break down or lose control, resulting in property losses and casualties. At present, emergency avoidance measures on highways mainly rely on escape lanes. Escape lanes are an emergency avoidance device specially designed for out-of-control vehicles. They are usually set up on long downhill sections or accident-prone areas to help out-of-control vehicles safely slow down and eventually stop to avoid more serious accidents.
[0003] Traditional brake beds for emergency lanes are generally paved with soft materials such as gravel and soil, which use the high friction and compression resistance of these materials to quickly reduce the speed of vehicles. However, this design has shortcomings such as limited deceleration effect, high maintenance cost, and poor adaptability. In order to solve the above problems, it is an urgent need for the current technological development to provide a more efficient, low-maintenance and well-adaptable brake bed for emergency lanes on highways.
[0004] Patent CN114481732B achieves emergency braking by setting a curve area in the middle area of the existing escape lane. The curve area includes a right-turn curve driving identification area (with a roller system), a side-slip deceleration area, and a sand and stone accumulation protection area. Patent CN112523020B provides a rear-flip front and rear wheel resistance reversal system. As soon as possible, the design and preparation methods of highway escape lanes are also constantly innovating. These new technologies still have certain limitations in practical applications, such as high cost and complex construction. Therefore, there is an urgent need for a new escape lane solution that comprehensively considers cost control, easy construction and maintenance, so as to meet the actual needs of highway safety management. Summary of the invention
[0005] In order to overcome the deficiencies in the prior art, the present application provides a concrete for a brake bed of a highway escape lane, and a preparation method and application thereof.
[0006] In a first aspect, the present application provides a concrete for a brake bed of a highway escape lane, specifically comprising the following components in parts by weight: specifically comprising the following components in parts by weight: 180-220 parts of cement, 40-60 parts of carbon mineralized mineral materials, 20-30 parts of lightweight aggregate, 3-7 parts of modified fiber, 0.4-0.8 parts of foaming agent, 0.02-0.06 parts of foam stabilizer, 2-6 parts of water reducer, and 100-150 parts of mixing water; The lightweight aggregate is prepared by mixing hollow glass microspheres with a particle size of 0.02-0.06 mm and ceramsite with a particle size of 1-3 mm in a weight ratio of 0.3-1:1; The preparation method of the modified fiber is as follows: polyvinyl alcohol fiber, propylene triethoxysilane and starch are mixed in a weight ratio of 100:3-7:12-20, placed in a 20-30° C., 2-6wt% boric acid aqueous solution for reaction for 24-72 hours, and dried to obtain the modified fiber.
[0007] The present application utilizes the above-mentioned technical scheme to prepare modified fibers, and by screening and specifying the amounts of cement, carbon mineralized mineral materials, lightweight aggregates, foaming agents, foam stabilizers, water reducers, and mixing water as raw material components of concrete, the prepared concrete for the brake bed of the highway safe lane has long-term stable crushing energy absorption, and has excellent maximum crushing depth and friction coefficient.
[0008] The lightweight aggregate uses hollow glass microspheres and expanded clay in a specific weight ratio and with specific specifications to optimize the pore structure during concrete preparation, ensure the uniform dispersion of each raw material component in the cement raw material, increase the number of active sites, promote the completeness of the mineralization reaction of carbon mineralized mineral materials, and at the same time improve the binding force of the modified fiber, thereby improving the performance of the concrete.
[0009] In the preparation method of the modified fiber, polyvinyl alcohol fiber, propylene triethoxysilane and starch are modified in a boric acid aqueous solution, so that the polyvinyl alcohol fiber can be first combined with starch with a certain viscosity, thereby improving the surface structure of the polyvinyl alcohol fiber, making it easier for the modified fiber to combine with other raw materials, thereby improving the dispersibility and bonding strength of the steel fiber in the concrete, reducing the slippage between the polyvinyl alcohol fiber and the concrete, making the concrete have excellent impact resistance and resistance, and reducing the probability of deeper crushing and cracking of the concrete due to impact force.
[0010] Preferably, the concrete for the brake bed of the highway escape lane specifically includes the following components in parts by weight: 190-210 parts of cement, 45-55 parts of carbon mineralized mineral materials, 22-27 parts of lightweight aggregate, 4-6 parts of modified fiber, 0.5-0.7 parts of foaming agent, 0.03-0.05 parts of foam stabilizer, 3-5 parts of water reducer, and 110-140 parts of mixing water.
[0011] Preferably, the preparation method of the modified fiber is: polyvinyl alcohol fiber, propylene triethoxysilane and starch are mixed in a weight ratio of 100:4-6:14-18, placed in a 20-30°C, 3-5wt% boric acid aqueous solution for reaction for 24-72h, and dried to obtain the modified fiber.
[0012] Preferably, the preparation method of the carbon mineralized mineral material is: weigh a total of 100-300 parts by weight of mineral material and 10-50 parts by weight of water, and put them into a grinding jar equipped with ball mill beads; inject 20%-100% CO2, the CO2 flow rate is 1-3L / min, and start grinding at 400-600rpm for 20-60min; then dry to constant weight, pound and sieve to obtain; the mineral material is selected from one or more of carbon mineralized yellow phosphorus slag, carbon mineralized magnesium slag and carbon mineralized cement clinker, carbon mineralized steel slag, and carbon mineralized carbide slag.
[0013] Adopt the technical scheme of the present application, the resource utilization efficiency of yellow phosphorus slag and magnesium slag is low, the environmental pollution is large, and the dust of cement clinker, steel slag and carbide slag is large, the efficiency is low, and the energy consumption is high. The wet grinding of appropriate water-solid ratio and the mode of carbon dioxide injection are adopted, under the mechanochemical coupling effect, the particle size of yellow phosphorus slag and magnesium slag becomes smaller, and the ion dissolution rate is accelerated, and calcite, aragonite and vaterite type CaCO3 are generated in the carbon mineralization reaction process, and the Mg ions of the existence of magnesium slag can also accelerate the generation of dolomite CaMg (CO3)2 generation, and these products are overlapped alternately, and act as reactants, nucleators and inert fillers with their larger specific surface area in the hydration process. The mechanochemical coupling effect will destroy the material surface passivation layer and form a new surface for carbon mineralization, further increase the absorption of carbon dioxide from the raw material end, reduce the carbon emission of the building materials industry, and have important environmental significance.
[0014] Preferably, the foaming agent is hydrogen peroxide with a mass concentration of 10-35%.
[0015] Preferably, the foam stabilizer is selected from one or more of methyl cellulose ether (MC), hydroxyethyl cellulose ether (HEC), hydroxyethyl methyl cellulose ether (HEMC), hydroxypropyl methyl cellulose ether (HPMC), stearate series foam stabilizers, styrene-butadiene emulsion, and ethylene-vinyl acetate emulsion.
[0016] Furthermore, the foam stabilizer is composed of a mixture of hydroxypropyl methylcellulose ether and styrene-butadiene emulsion in a weight ratio of 7:0.5-1.5.
[0017] Preferably, the mixing water is a sodium bicarbonate aqueous solution with a molar concentration of 0.10-0.75 mol / L.
[0018] The technical solution of the present application uses sodium bicarbonate aqueous solution as mixing water, so that the carbon dioxide absorption effect further increases the absorption of carbon dioxide, and the HCO3-rich - / CO3 2- It can accelerate the hydration of the slurry and play a role similar to that of an accelerating setting agent. There is no need to add additional accelerating components. It ensures early strength growth while improving mold utilization efficiency and production efficiency.
[0019] Preferably, the water reducer is selected from one or more of polycarboxylic acid water reducers and naphthalene water reducers.
[0020] In a second aspect, the present application provides a method for preparing the concrete for the brake bed of the highway escape lane, which specifically comprises the following steps in sequence: Weigh cement, carbon mineralized mineral material, lightweight aggregate and modified fiber, and mix them until uniform; Add mixing water, foam stabilizer and water reducer, stir at 200-600rpm for 60-600s, then stir at 1000-3000rpm for 10-60s; Add a foaming agent and stir at a speed of 1000-3000 rpm for 10-60 seconds to obtain a slurry; Pour the slurry into the mold and let it stand for 0.5-2 hours to foam; Place it in a curing room for 24-48 hours, then demould and continue curing for 28-180 days.
[0021] In a third aspect, the present application provides a highway escape lane brake bed, which is prepared using the above-mentioned highway escape lane brake bed concrete.
[0022] In a fourth aspect, the present application provides a method for preparing the above-mentioned highway escape lane brake bed, which specifically comprises the following steps in sequence: Transport the cured concrete blocks to the pre-paving location of the brake bed in the highway escape lane, tightly splice and assemble the modules one by one, and install the top cover on the modules; By laying and installing crash barriers, isolation facilities, guardrails, tow lanes, monitoring facilities, lighting facilities, deceleration and energy dissipation facilities, etc. around the brake bed along the exit ramp, a highway escape lane can be obtained.
[0023] In summary, the technical solution of this application has the following effects: The present application utilizes the above-mentioned technical scheme to prepare modified fibers, and by screening and specifying the amounts of cement, carbon mineralized mineral materials, lightweight aggregates, foaming agents, foam stabilizers, water reducers, and mixing water as raw material components of concrete, the prepared concrete for the brake bed of the highway safe lane has long-term stable crushing energy absorption, and has excellent maximum crushing depth and friction coefficient.
[0024] The technical solution of the present application, through specific screening of the types and specifications of lightweight aggregates and the preparation method of modified fibers, plays a synergistic role with carbon mineralized mineral materials to produce more excellent technical effects, thereby further improving the buffering performance of the prepared concrete.
[0025] The highway escape lane brake bed prepared by the technical solution of the present application has a maximum crushing depth of no more than 290mm, a crushing strength of 0.3-0.35MPa, and a friction coefficient of no less than 0.50. It can absorb energy by crushing for a long time and stably according to the design standards, provide the buffering effect required for emergency avoidance of various types of accident vehicles, and ensure the safety of vehicles and personnel.
[0026] The technical solution of this application facilitates the rapid splicing and installation of the module body, and can be tightly fixed together. It is equipped with conventional safety indication facilities, which reduces the engineering cost, improves the construction efficiency and the stability of the overall structure. After the brake bed of the highway escape lane is used, it can be directly replaced or repaired, which greatly reduces the use cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a schematic diagram of the components of the highway escape lane of the present application; the figure numbers are: 1-exit ramp; 2-crash barrier; 3-isolation facility; 4-guardrail; 5-obstruction lane; 6-monitoring facility; 7-lighting facility; 8-brake bed; 9-deceleration energy dissipation facility. DETAILED DESCRIPTION
[0028] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.
[0029] Yellow phosphorus slag comes from Guizhou Phosphate Chemical Plant; magnesium slag comes from a magnesium refinery in Yulin, Shaanxi; polycarboxylate water reducer is purchased from Jiangsu Subote New Materials Co., Ltd.; polyvinyl alcohol fiber and polypropylene fiber are purchased from Anhui Wanwei Group Co., Ltd.; styrene-butadiene emulsion is purchased from Shandong Shengkai Chemical Co., Ltd.; hydroxypropyl methylcellulose ether is purchased from Shijiazhuang Wenyu Wood Cellulose Trading Co., Ltd.; starch is purchased from Dezhou Gaofeng Starch Co., Ltd.; the remaining raw materials can be obtained commercially. Example
[0030] Examples 1-5 Examples 1-5 respectively provide a kind of concrete for the brake bed of a highway escape lane and a preparation method thereof.
[0031] The difference between the above embodiments is that the amount of each component in the concrete for the brake bed of the highway escape lane is different, as shown in Table 1.
[0032] The preparation method of the concrete for the brake bed of the highway escape lane in the above embodiment is as follows: Lightweight aggregate: It is made of hollow glass microspheres with a particle size of 0.02-0.06mm and ceramsite with a particle size of 1-3mm in a weight ratio of 0.7:1; Preparation of modified fiber: polyvinyl alcohol fiber, propylene triethoxysilane and starch are mixed in a weight ratio of 100g:5g:16g, placed in 1L of 4wt% boric acid aqueous solution at 25°C to react for 48h, and dried at 80°C to obtain the modified fiber.
[0033] Preparation of carbon mineralized mineral material: weigh a total of 2000g of mineral material (1500g of carbon mineralized yellow phosphorus slag, 500g of carbon mineralized magnesium slag), 250g of water, put into a grinding jar equipped with ball mill beads; inject 50% CO2, the CO2 flow rate is 2L / min, and start grinding at 200rpm for 40min; then dry to constant weight, pound and pass through a 75μm sieve to obtain; Weigh cement, carbon mineralized mineral material, lightweight aggregate and modified fiber, then pour into a mixer and mix for 40 seconds until uniform; Add 0.4 mol / L sodium bicarbonate aqueous solution, water, foam stabilizer hydroxypropyl methylcellulose ether, and polycarboxylate water reducer, stir at 400 rpm for 360 s, and then stir at 2000 rpm for 30 s; A hydrogen peroxide foaming agent with a mass concentration of 20% was added, and the mixture was stirred at a speed of 2000 rpm for 30 seconds to obtain a slurry; Pour the slurry into a 400mm×400mm×400mm mold and let it stand for 1 hour to foam; Place in the curing room for 36 hours, then demould and continue curing for 28 days.
[0034] Table 1 Amount of each component in the concrete for the brake bed of the highway escape lane in Examples 1-5 and Comparative Examples 1-3 Embodiment 6-9 Examples 6-9 respectively provide a kind of concrete for the brake bed of the escape lane of a highway and a preparation method thereof.
[0035] The difference between the above embodiment and embodiment 1 is that the types of lightweight aggregates are different, as shown below.
[0036] In Example 6, hollow glass microspheres with a particle size of 0.02-0.06 mm and ceramsite with a particle size of 1-3 mm are mixed in a weight ratio of 0.3:1.
[0037] In Example 7, hollow glass microspheres with a particle size of 0.02-0.06 mm and ceramsite with a particle size of 1-3 mm are mixed in a weight ratio of 1:1.
[0038] In Example 8, hollow glass microspheres with a particle size of 0.02-0.06 mm and ceramsite with a particle size of 1-3 mm are mixed in a weight ratio of 0.5:1.
[0039] In Example 9, hollow glass microspheres with a particle size of 0.02-0.06 mm and ceramsite with a particle size of 1-3 mm are mixed in a weight ratio of 0.8:1.
[0040] The remaining process parameters in the above embodiment are the same as those in embodiment 1.
[0041] Examples 10-15 Examples 10-15 respectively provide a kind of concrete for the brake bed of the escape lane of a highway and a preparation method thereof.
[0042] The difference between the above embodiment and embodiment 1 is that the preparation method of the modified fiber is different, as shown below.
[0043] In Example 10: Preparation of modified fiber: polyvinyl alcohol fiber, propylene triethoxysilane and starch were mixed in a weight ratio of 100g:3g:20g, placed in 1L of 4wt% boric acid aqueous solution at 25°C to react for 48h, and dried at 80°C to obtain the modified fiber.
[0044] In Example 11: Preparation of modified fiber: polyvinyl alcohol fiber, propylene triethoxysilane and starch were mixed in a weight ratio of 100g:7g:12g, placed in a 4wt% boric acid aqueous solution at 25°C to react for 48h, and dried at 80°C to obtain the modified fiber.
[0045] In Example 12: Preparation of modified fiber: polyvinyl alcohol fiber, propylene triethoxysilane and starch were mixed in a weight ratio of 100g:4g:18g, placed in 1L of 4wt% boric acid aqueous solution at 25°C to react for 48h, and dried at 80°C to obtain the modified fiber.
[0046] In Example 13: Preparation of modified fiber: polyvinyl alcohol fiber, propylene triethoxysilane and starch were mixed in a weight ratio of 100g:6g:14g, placed in 1L of 4wt% boric acid aqueous solution at 25°C to react for 48h, and dried at 80°C to obtain the modified fiber.
[0047] In Example 14: Preparation of modified fiber: polyvinyl alcohol fiber, propylene triethoxysilane and starch were mixed in a weight ratio of 100g:5g:17g, placed in 1L of 2wt% boric acid aqueous solution at 25°C to react for 48h, and dried at 80°C to obtain the modified fiber.
[0048] In Example 15: Preparation of modified fiber: polyvinyl alcohol fiber, propylene triethoxysilane and starch were mixed in a weight ratio of 100g:5g:17g, placed in 1L of 6wt% boric acid aqueous solution at 25°C to react for 48h, and dried at 80°C to obtain the modified fiber.
[0049] The remaining process parameters in the above embodiment are the same as those in embodiment 1.
[0050] Comparative Example Comparative Examples 1-3 Comparative Examples 1-3 respectively provide a kind of concrete and a preparation method thereof.
[0051] The difference between the comparative example and Example 1 is that the amounts of the components in the concrete for the brake bed of the highway escape lane are different, as shown in Table 1.
[0052] The remaining process parameters in the above comparative example are the same as those in Example 1.
[0053] Comparative Examples 4-6 Comparative Examples 4-6 respectively provide a kind of concrete and a preparation method thereof.
[0054] The differences between the above comparative example and Example 1 are specifically as follows.
[0055] In Comparative Example 4, the lightweight aggregate is prepared by mixing hollow glass microspheres with a particle size of 0.02-0.06 mm and ceramsite with a particle size of 4-8 mm in a weight ratio of 1:0.7.
[0056] In Comparative Example 5: the modified fibers were replaced by an equal amount of unmodified polyvinyl alcohol fibers.
[0057] In Comparative Example 6: In the method for preparing the modified fiber: an equal amount of polyethylene fiber is used instead of polyvinyl alcohol fiber to prepare the modified fiber.
[0058] The remaining process parameters in the above comparative example are the same as those in Example 1.
[0059] Performance testing After the concrete prepared in the embodiment and the comparative example were cured for 28 days, the crushing degree, shrinkage strength and friction coefficient were tested respectively.
[0060] The maximum crush depth detection method is as follows: according to the requirements of MH / T 5111-2015, the specimen is dried to constant weight and placed under the compression rod of the universal testing machine so that the center line of the specimen coincides with the axis of the compression rod. The universal testing machine is started and the crush depth during the compression process is recorded.
[0061] The method for testing the collapse strength is as follows: cut a 100mm×100mm×100mm specimen from the test block, dry the specimen to constant weight according to the requirements of MH / T5111-2015, then place the specimen in a cube constraint frame and under the compression rod of the universal testing machine, so that the center line of the specimen coincides with the axis of the compression rod, start the universal material testing machine, and draw the collapse curve of each age. This application takes the average value of the stress data at 15-45mm of the platform section of the collapse curve as the collapse strength.
[0062] The friction coefficient detection method is: refer to the pendulum instrument method of JTG 3450-2019 for detection and calculation.
[0063] Test results: as shown in Table 2.
[0064] Table 2 Performance test results of concrete in the examples and comparative examples Combined with Table 2, by comparing the performance test results of the concrete in the embodiment and the comparative example, it can be known that the maximum crushing depth of the concrete prepared by using the technical solution provided by the present application is ≤290mm, the collapse strength is 0.3-0.35MPa, and the friction coefficient is ≥0.55.
[0065] By comparing the performance test results of the concrete in Examples 1, 6-9 and Comparative Example 4, the present application selects a lightweight aggregate made by mixing hollow glass microspheres with a particle size of 0.02-0.06 mm and ceramsite with a particle size of 1-3 mm in a weight ratio of 0.3-1:1 as the raw material of concrete, which can further improve the performance of the concrete.
[0066] By comparing the performance test results of concrete in Examples 1, 10-15 with those in Comparative Examples 5-6, the present application selects a mixture of polyvinyl alcohol fiber, propylene triethoxysilane, and starch in a weight ratio of 100:3-7:12-20, and uses boric acid aqueous solution as a solvent to prepare modified fibers, which can further improve the performance of concrete.
[0067] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A concrete for a brake bed of a highway escape lane, characterized in that: Specifically, it includes the following components in parts by weight: 180-220 parts of cement, 40-60 parts of carbon mineralized mineral materials, 20-30 parts of lightweight aggregate, 3-7 parts of modified fiber, 0.4-0.8 parts of foaming agent, 0.02-0.06 parts of foam stabilizer, 2-6 parts of water reducer, and 100-150 parts of mixing water; The lightweight aggregate is prepared by mixing hollow glass microspheres with a particle size of 0.02-0.06 mm and ceramsite with a particle size of 1-3 mm in a weight ratio of 0.3-1:1; The preparation method of the modified fiber is as follows: polyvinyl alcohol fiber, propylene triethoxysilane and starch are mixed in a weight ratio of 100:3-7:12-20, placed in a 20-30° C., 2-6wt% boric acid aqueous solution for reaction for 24-72 hours, and dried to obtain the modified fiber.
2. The concrete for brake bed of highway escape lane according to claim 1 is characterized in that: Specifically, it includes the following components in parts by weight: 190-210 parts of cement, 45-55 parts of carbon mineralized mineral materials, 22-27 parts of lightweight aggregate, 4-6 parts of modified fiber, 0.5-0.7 parts of foaming agent, 0.03-0.05 parts of foam stabilizer, 3-5 parts of water reducer, and 110-140 parts of mixing water.
3. The concrete for brake bed of highway escape lane according to claim 1 is characterized in that: The preparation method of the modified fiber is as follows: polyvinyl alcohol fiber, propylene triethoxysilane and starch are mixed in a weight ratio of 100:4-6:14-18, placed in a 3-5wt% boric acid aqueous solution at 20-30°C for reaction for 24-72h, and dried to obtain the modified fiber.
4. The concrete for brake bed of highway escape lane according to claim 1 is characterized in that: The preparation method of the carbon mineralized mineral material is as follows: weigh a total of 100-300 parts by weight of mineral material and 10-50 parts by weight of water, and put them into a grinding jar equipped with ball mill beads; inject 20%-100% CO2, with a CO2 flow rate of 1-3L / min, and start grinding at 400-600rpm for 20-60min; then dry to constant weight, pound and sieve to obtain the material; the mineral material is selected from one or more of carbon mineralized yellow phosphorus slag, carbon mineralized magnesium slag and carbon mineralized cement clinker, carbon mineralized steel slag, and carbon mineralized carbide slag.
5. The concrete for brake bed of highway escape lane according to claim 1 is characterized in that: The foaming agent is hydrogen peroxide with a mass concentration of 10-35%.
6. The concrete for brake bed of highway escape lane according to claim 1, characterized in that: The foam stabilizer is selected from one or more of methyl cellulose ether, hydroxyethyl cellulose ether, hydroxyethyl methyl cellulose ether, hydroxypropyl methyl cellulose ether, stearate series foam stabilizers, styrene-butadiene emulsion, and ethylene-vinyl acetate emulsion.
7. The concrete for brake bed of highway escape lane according to claim 1, characterized in that: The mixing water is a sodium bicarbonate aqueous solution with a molar concentration of 0.10-0.75 mol / L.
8. The method for preparing concrete for brake bed of highway escape lane according to any one of claims 1 to 7, characterized in that: Specifically, the following steps are performed in sequence: Weigh cement, carbon mineralized mineral material, lightweight aggregate and modified fiber, and mix them until uniform; Add mixing water, foam stabilizer and water reducer, stir at 200-600rpm for 60-600s, then stir at 1000-3000rpm for 10-60s; Add a foaming agent and stir at a speed of 1000-3000 rpm for 10-60 seconds to obtain a slurry; Pour the slurry into the mold and let it stand for 0.5-2 hours to foam; Place it in a curing room for 24-48 hours, then demould and continue curing for 28-180 days.
9. A brake bed for a highway escape lane, characterized in that: The highway escape lane brake bed is prepared using the concrete described in any one of claims 1 to 7.
10. The method for preparing the brake bed for the highway escape lane according to claim 9, characterized in that: Specifically, the following steps are performed in sequence: Transport the cured concrete blocks to the pre-paving location of the brake bed in the highway escape lane, tightly splice and assemble the modules one by one, and install the top cover on the modules; By laying and installing crash barriers, isolation facilities, guardrails, tow lanes, monitoring facilities, lighting facilities, deceleration and energy dissipation facilities, etc. around the brake bed along the exit ramp, a highway escape lane can be obtained.
Citation Information
Patent Citations
A type of rear-tilt front and rear wheel resistance reversal structure for highway emergency escape lanes
CN112523020B
Modified PVC material
CN106633482A
Production method of waterproof and heat-preservation integrated grouting filling mortar
CN107857541A
Lightweight high-strength concrete and preparation method thereof
CN112521095A
Limestone powder composite admixture as well as preparation method and application thereof
CN115557765A